Establishment of management policy of personnel in enterprises (in the example of Angren coal mine in Uzbekistan) (Вестник транспорта - Transport xabarnomasi, 2026)
An essential element of any business’s efficient operation is people management. Establishing efficient human management practices is especially important for businesses in high-demand industries like mining in Uzbekistan, where industrial development is a major factor in economic growth. The process of creating people management policies at Angren Coal Mine, one of the top coal extraction companies in Uzbekistan, is examined in this thesis. The study examines the problems, tactics, and results of human management today and makes suggestions for raising employee happiness and organizational effectiveness.